Valuable Nutrients from Ulva rigida: Modulation by Seasonal and Cultivation Factors - Ana S. Queirós; Ana R. Circuncisão; Eduarda Pereira; Mónica Válega; Maria H. Abreu; Artur M. S. Silva; Susana M. Cardoso (Applied Sciences, 2021)
Ulva macroalgae species are recognized to be an underexploited source of key nutrients, including proteins, fibers and minerals. The present work evaluated the nutritional value protein, ash, mineral composition, fat, fatty acid profile and dietary fiber of the green macroalgae Ulva rigida produced in an open land-based integrated multi-trophic aquaculture (IMTA) system, over four seasons. Overall, protein and fat content of the farmed algae ranged between 7.6 and 25.8% DW and between 0.2 and 1.3% DW, respectively, reaching the highest levels during autumn/winter seasons. In turn, total dietary fiber and ashes showed a contrary seasonal tendency, reaching maximum levels in spring (40.9–58.3% DW and 25.5–38.8% DW, respectively). Notably, the latter were particularly characterized by their richness in potassium, magnesium and iron, and a sodium/potassium ratio bellow 1.7. Variable cultivation conditions of stocking density (Sd) and flow rate (Fr) were also tested, allowing to confirm that manipulation of cultivation conditions in an IMTA system may help to improve the nutritional value of this macroalga and to boost its market value through its use as a functional food ingredient.